Development of Discovery Learning-Based Student Worksheets to Improve Critical Thinking in Fifth Grade Mathematics - Fitriyani, Fitriyani; Nurhanurawati, Nurhanurawati; Perdana, Ryzal; Rohman, Fatkhur (Journal of Innovation and Research in Primary Education, 2025)
The purpose of this project is to develop valid, practical, and efficient student worksheets that enhance students' critical thinking skills by applying Discovery Learning principles. This research falls into the category of research and development, or R&D, and uses the Borg and Gall model. The population of this study consisted of fifth-grade students from MIN 1 West Lampung. Sampling was conducted purposively, consisting of 28 students from fourth-grade A and 28 students from fourth-grade B of MIN 1 West Lampung. Questionnaires and tests were used as data collection methods in this study. Discovery Learning-based student worksheets went through a trial phase that included testing the practicality of educators' and students' answers, as well as validation by evaluation, material, media, and language experts. The validation results from material experts obtained a percentage score of 62% with a fairly valid category, media experts obtained a percentage score of 87% with a very valid category, language experts obtained a score of 82% with a very valid category, and question evaluation experts obtained a percentage score of 92% with a very valid category. In the practicality test, the average percentage value of educators' answers obtained a percentage score of 91% with very practical criteria, while the average percentage of students' answers obtained a percentage score of 88% with very practical criteria. The data analysis technique used an independent sample t-test with a calculation result of <0.001 <0.05, meaning that there is a significant difference between the critical thinking abilities of the experimental class and the control class. Based on the data obtained from the results of the study, it can be concluded that the discovery learning-based student worksheets is valid, practical, and effective in improving students' critical thinking abilities.